2017
DOI: 10.1186/s40623-017-0706-3
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic receiver with capacitive electrodes and triaxial induction coil for tunnel exploration

Abstract: A new type of electromagnetic (EM) receiver has been developed by integrating four capacitive electrodes and a triaxial induction coil with an advanced data logger for tunnel exploration. The new EM receiver can conduct EM observations in tunnels, which is one of the principal goals of surface-tunnel-borehole EM detection for deep ore deposit mapping. The use of capacitive electrodes enables us to record the electrical field (E-field) signals from hard rock surfaces, which are high-resistance terrains. A compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…These advances include modifications to current sensing technologies and adaptations of new types of EM sensors for measurements. For example, Kai et al (2017) have developed a new type of EM receiver by combining four capacitive electrodes and a triaxial induction coil for conducting EM observations in tunnels. In addition, new types of EM sensors, such as optical-fiber EM sensors (e.g., Sato and Takayama 2007;Layeghi et al 2014), microelectromechanical system (MEMS) magnetic sensors (e.g., Campbell and Atekwana 2018), fluxgate magnetic sensors (e.g., Bartington and Chapman 2004; Ramasamy and Mo-hanty 2020), superconducting quantum interference devices (SQUIDs) (e.g., Du et al 2018), and non-contact electric field instruments (e.g., Knudsen et al 2017) also provide future alternative ways to measure electric and magnetic fields with lighter weights, smaller volumes, and better resolutions than are currently the norm.…”
Section: Prospects For Em Exploration Techniquesmentioning
confidence: 99%
“…These advances include modifications to current sensing technologies and adaptations of new types of EM sensors for measurements. For example, Kai et al (2017) have developed a new type of EM receiver by combining four capacitive electrodes and a triaxial induction coil for conducting EM observations in tunnels. In addition, new types of EM sensors, such as optical-fiber EM sensors (e.g., Sato and Takayama 2007;Layeghi et al 2014), microelectromechanical system (MEMS) magnetic sensors (e.g., Campbell and Atekwana 2018), fluxgate magnetic sensors (e.g., Bartington and Chapman 2004; Ramasamy and Mo-hanty 2020), superconducting quantum interference devices (SQUIDs) (e.g., Du et al 2018), and non-contact electric field instruments (e.g., Knudsen et al 2017) also provide future alternative ways to measure electric and magnetic fields with lighter weights, smaller volumes, and better resolutions than are currently the norm.…”
Section: Prospects For Em Exploration Techniquesmentioning
confidence: 99%
“…To evaluate the performance of the full waveform current recorder in field conditions, we conducted field ore exploration experiments on Linxi county, which is in northern China. A total of 15 EMR6 EM receivers (Chen et al, 2017) and two EMT48 multifunction transmitters (Wang et al, 2018) were deployed for the field work. The EM receivers and transmitters were set as multifunction to support many electrical prospecting methods, such as TDIP, SIP, CSAMT, and PRS mode data acquisition.…”
Section: Field Experimentsmentioning
confidence: 99%
“…However, when a single component (E field or B field) is used to calculate a normalised field, the current data must be calculated for data postprocessing. This requires the current signal to be recorded with high precision (Constable, 2013). For TDIP applications, the load of the transmitter is not stable due to variable grounding resistance in field conditions, and the real current amplitude is not constant.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations such as highly resistive terrains, coils that are too long to fit in a narrow tunnel space, and the absence of a GPS signal make it difficult to use conventional surface EM receivers to measure the signal inside tunnels. In their work "Electromagnetic receiver with capacitive electrodes and triaxial induction coil for tunnel exploration, " Kai et al (2017) introduced capacitive electrodes and triaxial induction coils that help avoid these limitations. They successfully developed their new design, and their tests in a mine showed that the new equipment can be used to measure EM signals inside tunnels with typical noise characteristics.…”
Section: Engineering Applicationsmentioning
confidence: 99%